Renewable energy transition and economic development in the united Kingdom - Tran Van Hung (Discover Sustainability)
Abstract Given that the effect of the synergy between natural resources and environmental sustainability varies by country and economic structure, this study examines the dynamic impacts of FDI, mineral markets, GDP, NORE, FID, REN, and EB on the ENT in the UK. It makes contributions to the related literature by (i) revisiting this question for the energy transition in the UK and (ii) using QQR and NCQ to detail the interplay between the time series. The empirical outcomes highlight that renewable energy, FDI, FID, and urbanization have a tremendous impact on this country's energy transition, which supports sustainable development goals. Results also show a mixed reaction of GDP, non-renewable energy, and mineral markets to the energy transition in the UK. These findings offer insightful policy suggestions for all interested parties to advance the shift to REN for low-carbon and environmentally friendly growth.